Un ponte, un porto, un mare. Roma Termini e i suoi margini - Silvia Antinori (lo Squaderno)
Full of paradoxes, characterized by the co-presence of contrasting realities, the territory of Termini Station is a threshold and an extreme mirror of processes that characterize in different ways the con-temporary world, a place which, through its socio-spatial morphologies, deeply and in many senses interrogates the urban dimension and the relations with other elements that compose the making of the city. Located in the heart of Rome, it is a territory in ongoing transformation, daily crossed by thou-sands of passengers and city users, while, at the same time, it is a place innervated by social margins inhabited by different populations; a place where transit, marginality, informality, control, and consump-tion intermingle. Through the words of some social workers of services for homeless people in the ter-ritory, the station area is sketched as a liquid borderland, a sea, a place of conjunction, in which, how-ever, emotional charges, memories, social and symbolic ties are projected, nuances and historical stratifications take body - deflating the classic notion of “non-place.” The station becomes a central hub of a myriad of maps marked by the routes of those who transit there, and those who, for various rea-sons, spend most of their time in the area; it becomes the center of formal and informal practices, mi-gration paths, plural geographies, and forms of belonging, illuminating a tension between different ways of practicing the same space.